Physiological demands, morphological characteristics, physical abilities and injuries of female soccer players - Milanovic, Z.; Sporis, G.; James, N.; Trajkovic, N.; Ignjatovic, A.; Sarmento, H.; Trecroci, A.; Borges Mendes, B. M. (Journal of Human Kinetics, 2017)
The popularity of female soccer is increasing as well as the number of females playing soccer. Similarly, over the last twenty or so years, research in soccer has increased significantly, but a large disparity exists in the volume of studies involving male and female players. As a consequence of this, female players remain less well understood compared to males. The purpose of the present narrative review was to describe morphological characteristics, physiological demands, physical abilities and injuries in female soccer players. Physiological demands are similar between men`s and women`s soccer, but competitive women`s matches were characterized by nearly 33% less distance covered, although at higher intensity levels (maximum speeds greater than 15 km/h) than typically found in the men`s game. Sub-elite female players also tended to run less at higher intensity levels at the end of both halves in comparison with elite female players. High intensity running is an important factor of success in soccer since many critical moments of the game occur under this condition. The ability to rapidly change direction also determined elite, sub-elite and amateur levels. The implementation of functional training, which focused on soccer-specific drills and plyometric exercises, to improve explosive power, may improve conditioning in female soccer players as well as decrease the risk of injuries which was 3-8 times higher in females compared to males. This review presents an in-depth overview of the most influential factors for determining success in female soccer.